Exergoeconomic assessment of the optimized vapour-recompression assisted column for palmbased fatty acid fractionation - Norul Malakiah, Sidek; Mohamad Rizza, Othman (Elsevier B.V., 2022)
In our preliminary study (Sidek and Othman, 2020), vapour recompression (VRC) proved to have a promising energy performance in the case of palm kernel oil (PKO) fatty acid fractionation. This paper extends the research by applying an exergy analysis as well as incorporating four vacuum fractionation columns to represent a real industry application. The study also included a two-step optimization approach based on response surface methodology. All configurations were evaluated for their exergetic and economic performances. Due to the high costs and low efficiency, the optimised VRC-assisted columns are not in favour of this study. The standard VRC-assisted columns, though exhibit a higher CAPEX than the conventional columns, are more thermodynamically efficient and demonstrate a substantial reduction of 84-88% in OPEX. A thorough optimisation study is needed for future works.